2009
DOI: 10.1258/acb.2009.008231
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum glycated albumin to haemoglobin A1Cratio with hepatic function tests in patients with chronic liver disease

Abstract: Background: In patients with chronic liver disease (CLD), glycated haemoglobin (HbA 1C ) levels have been shown to be apparently lower than real values, whereas serum glycated albumin (GA) levels are apparently higher. The present study was aimed to examine whether both glycaemic indices are influenced by hepatic function. Methods: Subjects consisted of 82 patients with CLD. Various indicators for hepatic function as well as HbA 1C and GA were also measured. Estimated HbA 1C values were calculated from the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…HbA1c level in patients with HCC is higher than in patients with liver cirrhosis or in control subjects [81] . In patients with liver cirrhosis, however, HbA1c does not properly represent glycemic control status in cirrhotic patients because of the short lifespan of erythrocytes caused by hypersplenism [82][83][84][85][86] . These data indicate that assessment and management of hepatogenous DM using HbA1c is inaccurate, although poor glucose control is associated with HCC incidence.…”
Section: Assessment Of Dm In Patients With Liver Diseasementioning
confidence: 99%
“…HbA1c level in patients with HCC is higher than in patients with liver cirrhosis or in control subjects [81] . In patients with liver cirrhosis, however, HbA1c does not properly represent glycemic control status in cirrhotic patients because of the short lifespan of erythrocytes caused by hypersplenism [82][83][84][85][86] . These data indicate that assessment and management of hepatogenous DM using HbA1c is inaccurate, although poor glucose control is associated with HCC incidence.…”
Section: Assessment Of Dm In Patients With Liver Diseasementioning
confidence: 99%
“…Bando et al [7] previously reported that the GA/HbA1c ratio in patients with CLD have an inverse correlation with the some indicators of hepatic function, regardless of the mean plasma glucose levels, thus suggesting that the increase of GA/HbA1c ratio indicates a reduction in the liver function caused by the progression of liver cirrhosis. Consistent with that report, our current histological evaluation revealed that the GA/HbA1c ratios of the cirrhotic patients were significantly higher than those of the patients without cirrhosis (Figure 2A).…”
Section: Discussionmentioning
confidence: 97%
“…Since HbA1c shows lower and GA shows higher values in CLD patients, the GA/HbA1c ratio is thought to be high in patients with liver cirrhosis. Indeed, the GA/HbA1c ratio in patients with CLD has been reported to show an inverse correlation with some indicators of hepatic function (including the hepaplastin test, cholinesterase and bilirubin) independent of the mean plasma glucose levels, thus suggesting that the GA/ HbA1c ratio increases as the liver cirrhosis progresses [7] . However, it has not been examined whether the GA/ HbA1c ratio correlates with the histological fibrotic stage in CLD patients.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with chronic liver diseases HbA 1c levels may be underestimated, whereas both fructosamine and glycated albumin levels may show a false increase, due to prolonged albumin half-life [40][41][42]. An indicator was proposed for glycaemia control monitoring in patients with diabetes and concomitant liver disease, described as a mean value of HbA 1c and GA [42].…”
Section: Clinical Relevance Of Gamentioning
confidence: 99%
“…An indicator was proposed for glycaemia control monitoring in patients with diabetes and concomitant liver disease, described as a mean value of HbA 1c and GA [42].…”
Section: Clinical Relevance Of Gamentioning
confidence: 99%